Sistem Pengaman Brankas Menggunakan Sensor Fingerprint Dan Remot Kontrol Rf Berbasis Arduino Uno - ANDAR CAHYONO, FAJAR; , Bambang Hari P, ST.,MT (2016)
In the present study the researchers made an electronic device related security systems that utilize the fingerprint as well as the remote control to open the safe door. Because in today's world a lot of theft is very detrimental to the public, the researchers created a security device safe. Making the security system is done by utilizing the fingerprint sensor and remote control rf as access opens the door safe so as not to be in collapse by thieves. Systems on the security appliance is managed by a microkontroller ie arduino uno. This tool uses rf remote control that is used to drive a servo motor to open the access door located the room where the fingerprint sensor. As well as a fingerprint sensor to obtain user data input fingerprint safes, fingerprint data is input from fingerprint sensors are set by arduino uno to drive a solenoid lock safes that can open the main door. Results of system security is the creation of a safe that is equipped with remote controls of rf and a fingerprint sensor for access opens the door safe, a system is made so that thieves can not open the door safe so that the goods are in safe stay safe from acts the